Changes in gut microbiota structure and function in gout patients - Zhao, Feiyan; Zhao, Zhixin; Man, Dafu; Sun, Zhihong; Tie, Ning; Li, Hongbin; Zhang, Heping (Food bioscience, 2023)
Gout is a metabolic disease caused by hyperuricemia resulting from purine metabolism disorder. It mainly manifests as joint pain or inflammation caused by urate crystal deposition in joints. Some recent studies have revealed the potential of gut microbiota in regulation of purine metabolism and body inflammation, suggesting gut microbiota can become the target for gout prevention and treatment. This study is a preliminary trial investigating the role of probiotics in the adjuvant treatment of gout and providing reference data for the selection of probiotics for use in further clinical trials. In total, 40 male participants were recruited (gout = 20, healthy controls = 20). The characteristics of gut microbiota in gout patients and the relationship between gut microbiota and gout-related clinical indices were explored. The results showed (1) lower microbiota diversity and microecological disturbance in the gut of gout patients (P < 0.001) (2) changes in gut microbiota (e.g., Faecalibacterium prausnitzil, Bacteroides uniformis, Lachnospira eligens); affected several metabolic pathways, such as uric acid metabolism and purine metabolism, which may modify the levels of active metabolites such as cholate and cholesterol in the body; (3) strong correlations between key differential species and the uric acid level, and key differential species may be used as probes for detecting uric acid metabolism to treat and prevent gout. Overall, our research proved the crucial relationship between gut microbiota and gout, thereby providing direction and scientific guidance for next clinical trials.